Advancements in neuroregenerative and neuroprotective therapies for traumatic spinal cord injury - Fischer, Gregor; Bättig, Linda; Stienen, Martin N.; Curt, Armin; Fehlings, Michael G.; Hejrati, Nader (Frontiers in Neuroscience, 2024)
Traumatic spinal cord injuries (SCIs) continue to be a major healthcare concern, with a rising prevalence worldwide. In response to this growing medical challenge, considerable scientific attention has been devoted to developing neuroprotective and neuroregenerative strategies aimed at improving the prognosis and quality of life for individuals with SCIs. This comprehensive review aims to provide an up-to-date and thorough overview of the latest neuroregenerative and neuroprotective therapies currently under investigation. These strategies encompass a multifaceted approach that include neuropharmacological interventions, cell-based therapies, and other promising strategies such as biomaterial scaffolds and neuro-modulation therapies. In addition, the review discusses the importance of acute clinical management, including the role of hemodynamic management as well as timing and technical aspects of surgery as key factors mitigating the secondary injury following SCI. In conclusion, this review underscores the ongoing scientific efforts to enhance patient outcomes and quality of life, focusing on upcoming strategies for the management of traumatic SCI. Each section provides a working knowledge of the fundamental preclinical and patient trials relevant to clinicians while underscoring the pathophysiologic rationale for the therapies.